Patients' ability to read and understand dosing instructions of their own medicines - a cross sectional study in a hospital and community pharmacy setting - M. G. C. A. Manchanayake; G. R. W. S. K. Bandara; N. R. Samaranayake (BMC, 2018)
Abstract Background Poor communication of medicines information to patients may cause medication errors. We assessed the completeness and readability of dosing instructions provided by pharmacists on dispensing labels and knowledge among patients on dosing instructions of their medicines. Methods A cross sectional study was conducted in a selected teaching hospital, and a community pharmacy, among 800 patients selected through a systematic sampling method, during a period of 2 months. Completeness of dosing instructions were assessed against a checklist. Patients were asked to read dosing instructions to assess readability. Patient knowledge on dosing instructions were determined through a questionnaire. Completeness, readability and knowledge were scored out of 10 for each dispensing label. Results A total of 1200 and 1372 dispensing labels were assessed in the hospital and community settings respectively. The median score out of 10, for completeness, readability and patient knowledge of dosing instructions were 6.7, 8.3 and 7.5 respectively in the hospital, and 7.5, 8.0 and 7.5 respectively in the community. Only a few dispensing labels had the route of administration (hospital, 0.5%; community, 0.8%) and the duration of treatment written (hospital, 0.25%; community, 0.65%) on them. Name (hospital, 48%; community, 27.3%) and strength (hospital, 40.2%; community, 36.6%) of medicines on dispensing labels were frequently misread. In both settings, readability scores significantly differed with education level (P < 0.001). Conclusions Some important dosing instructions were missing in dispensing labels. Readability of dosing instructions by patients was also not 100% and differed by their education level. Pharmacists did not adhere to a standard procedure in providing dosing instructions leading to communication gaps with patients. Hence we recommend the development of a standard procedure to provide complete, clear and simple dosing instructions to patients, and continuous training for pharmacists on proper communication of dosing instructions to patients.